Theme Basic/Survival Reading Skills - Wisconsin State Reading Association, West Allis; Jund, Suzanne; Wisconsin State Reading Association, West Allis ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
The five articles contained in this journal issue deal with basic/survival reading skills. Specific topics covered in the articles are an overview of survival reading, the reading habits of college students, a principal's view of reading instruction, a healthy self-concept as a basic survival skill, and a readability rating list for teacher-made materials. Regular journal features include a research update on accountability and the basics, a list of survival skills materials for use by teachers, reviews of professional materials, and a discussion of the role of parents in child language development. (FL)
Wisconsin State Reading Association Journal, v23 n1 Entire Issue Oct 1978.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Language; College Students; Elementary Secondary Education; Functional Reading; Higher Education; Literacy; Parent Role; Readability; Reading Instruction; Reading Interests; Reading Research; Reading Skills; Self Concept; Teacher Developed Materials; Survival Reading; Journal Articles